Total Sulfur Levels in Refined Petroleum Products of Southwestern Nigeria Using UV/VIS Spectrophotometer - Olatunji, Samuel; Adeniran, Jamiu Adetayo; Fakinle, Bamidele Sunday; Sonibare, Jacob (Taylor & Francis, 2020)
International Journal of Taylor and Francis,P.102-109